Small-diameter p-type SnS nanowire photodetectors and phototransistors with low-noise and high-performance. (7th January 2022) - Chen, Ruoling; Li, Long; Jiang, Long; Yu, Xiangxiang; Zhu, Desheng; Xiong, Yan; Zheng, Dingshan; Yang, Wenxing
Abstract: P-type nanostructured photodetectors and phototransistors have been widely used in the field of photodetection due to their excellent electrical and optoelectronic characteristics. However, the large dark current of p-type photodetectors will limit the detectivity. Herein, we synthesized small-diameter single-crystalline p-type SnS nanowires (NWs) and then fabricated single SnS NW photodetectors and phototransistors. The device exhibits low noise and low dark current, and its noise current power is as low as 2.4 × 10 −28 A 2 . Under 830 nm illumination and low power density of 0.12 mW cm −2, the photoconductive gain, responsivity and detectivity of the photodetector are as high as 3.9 × 10 2, 2.6 × 10 2 A W −1 and 1.8 × 10 13 Jones, respectively, at zero gate voltage. The rise and fall time of response are about 9.6 and 14 ms. The experimental results show that the small-diameter p-type SnS NWs have broad application prospects in high-performance and low-power photodetectors with high sensitivity, fast response speed and wide spectrum detection in the future.